Pengaruh Destination Image, Perceived Value, dan Satisfaction Terhadap Tourist Loyalty di Pantai Lon-Malang Kabupaten Sampang - Tia Astaivada; Pribanus Wantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of destination image, perceived value, and satisfaction on tourist loyalty at Lon Malang Beach, Sampang Regency. This type of research is quantitative research with analysis using Structural Equation Modeling using the SmartPLS version 4 statistical program. In this study, the population used is not known for certain (infinite) and the sample used is tourists who visit Lon Malang Beach. This study uses a questionnaire with a Likert scale. The results of the study obtained are that destination image has a strong influence on loyalty, but destination image has no effect on satisfaction. While perceived value also has no effect on loyalty, but perceived value has a strong influence on satisfaction. Likewise, satisfaction also has a positive effect on loyalty. So overall, destination image and perceived value play an important role in building loyalty and satisfaction at Lon Malang Beach in Sampang Regency, but the influence varies depending on the path tested. While satisfaction has a strong influence on tourist loyalty.